RELIABILITY TECHNIQUES FOR RFID: RELIABILITY TECHNIQUES FOR RFID - Kazhakov, Stefan; Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Radio Frequency Identification (RFID) technology has the potential to dramatically improve numerous industrial practices. However, it still faces many challenges, including security and reliability, which may limit its use in many application scenarios. While security has received considerable attention, reliability has escaped much of the research scrutiny. Radio Frequency Identification (RFID) technology is growing rapidly across many different industries. Developers apply the technology not only in traditional applications such as asset or inventory tracking, but also in security services such as electronic passports and RFID-embedded credit cards. However, RFID technology also raises a number of concerns regarding privacy and security.